COMPARISON OF THE EFFECTIVENESS OF EXTRACORPOREAL SHOCKWAVE THERAPY (ESWT) AND TADALAFIL ON ORGANIC ERECTILE DYSFUNCTION - Wiradinata, Indra; Zulfiqar, Yefri; Myh, Etriyel; Hardisman (Indonesian Urological Association, 2020)
Objective: To find a comparison of the effectiveness of ESWT and Tadalafil on organic erectile dysfunction. Material & Methods: This is a Quasi Experiment study that was carried out from February 2018 to April 2018. ESWT treatment was performed in Urology Outpatient Clinic. Cialis 10 mg was used in cased of Tadalafil. The sample size is 40 patients consists of 20 patients each treatment. The data was processed with a significance limit of p<0.05. Results: The sample age average is 61.7 years, the level of total cholesterol is 191 mg/dL, FBG 112.5 mg/dL, 2hPPBG 134.5 mg/dL, HDL 44.9 mg/dL, LDL 137.5 mg/dL, ureum 27 mg/dL, and creatinin 0.8 mg/dL. The proportion of Diabetes Mellitus patients in this study is 50% and hypertension 57.5%, which is 15% of them belong to mild erectile dysfunction category, 37.5% mild to moderate, 5% moderate, and 42.5% severe. We found an increasement of EHS on 75% patients that were treated with ESWT and 5% on patient that were treated with Tadalafil, and it is statistically significant (p<0.05). Conclusion: We found that ESWT and Tadalafil can increase EHS of organic erectile dysfunction patients, which ESWT is more effective than Tadalafil.